2022
DOI: 10.3389/fimmu.2022.882796
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Safety and Immunogenicity of Duck-Plague Virus gE Mutants

Abstract: Duck plague (DP) is an acute infectious disease in the duck industry. The duck plague virus (DPV) is the pathogen, a subfamily of alphaherpesvirinae. gE is a type I membrane protein that contains three parts: an extracellular domain, a transmembrane domain, and a cytoplasmic domain. gE is the major virulence determinant of α-herpesvirus. However, the functions of the gE extracellular and cytoplasmic domains have not been reported in DPV. In this study, a gE extracellular domain deletion mutant and a gE cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…In practical production, duck embryonic attenuated vaccine and chicken embryo fibroblast vaccine are mainly used to control duck plague ( 14 , 28 , 29 ). Previous studies have shown that the deletion of viral genes or gene functional domains can reduce the virulence of herpes virus, have no pathogenicity or weaken pathogenicity to natural hosts, and can achieve protective effects, which can be used for further genetic engineering vaccine research ( 23 , 30 , 31 ). In this study, based on the constructed CHv-ΔgC single-gene deletion strain, the gE gene was deleted using the BAC gene editing system ( 24 ), and an attenuated CHv-ΔgC/gE strain with double gene deletion was obtained.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In practical production, duck embryonic attenuated vaccine and chicken embryo fibroblast vaccine are mainly used to control duck plague ( 14 , 28 , 29 ). Previous studies have shown that the deletion of viral genes or gene functional domains can reduce the virulence of herpes virus, have no pathogenicity or weaken pathogenicity to natural hosts, and can achieve protective effects, which can be used for further genetic engineering vaccine research ( 23 , 30 , 31 ). In this study, based on the constructed CHv-ΔgC single-gene deletion strain, the gE gene was deleted using the BAC gene editing system ( 24 ), and an attenuated CHv-ΔgC/gE strain with double gene deletion was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Duck embryo fibroblasts (DEFs) were prepared from 9-day-old duck embryos and cultured in DMEM medium (Gibco, Shanghai, China) containing 10% neonatal bovine serum (NBS, Gibco, Rockford, USA) according to conventional methods ( 23 ). Duck plague virus Chinese virulent strain (CHv) (GenBank: NO.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations